(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article presents the results of phenological observations of medicinal, essential oil, and ornamental plant species cultivated in Chuy Valley. The timing of seedling emergence, flowering, fruiting, and dormancy is documented. The data obtained reflect the plants’ adaptability to the region’s harsh continental climate and allow conclusions to be drawn about their cultivation prospects.